AN ANALYSIS OF LEARNERS’ STRATEGIES AND LEARNERS’ MOTIVATION OF LEARNING VOCABULARY; A CASE STUDY AT THE FOURTH SEMESTER STUDENTS OF ENGLISHEDUCATION DEPARTMENT AT UNIVERSITY OF GUNUNG RINJANI (UGR) - RASYID RIDHO HAMIDY (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2020)
This thesis aimed at finding out what vocabulary learning strategies do fourth semester studentsof English Education program at University of Gunung Rinjani (UGR) use and how do studentscorrelation between second language learning motivation and vocabulary learning strategy use.This is qualitative research. The sample of this research was the fourth semester of UGR, in thisresearch the researcher took 10 students as samples.. To collect the data, the writer applied theclose interview. After collecting and calculating the data, the researcher found out that thestudents use mainly the same strategies, but there are some interesting exceptions. Somestudents mention using several different strategies but most use only a few of the most popularstrategies and have not altered the strategies when they have matured or advanced with theirlanguage studies. The advanced technology is becoming a meaningful part of vocabularylearning and second language learners have taken the initiative to use the possibilities providedby the technological innovations in order to develop their language skills, so in addition, usingtranslation was clearly a popular strategy even though there were some different methods ofusing it. And Students who have been successful in their language studies describe theirmotivation being high and they also employ a wider range of vocabulary strategies than theirless motivated and less successful peers even though there can be some exceptions andindividual differences.So this research suggested that Therefore lecturers should enhance themeaning of learning strategies and offer the opportunity to get to know and try out the differentstrategies in campus so that each learner can find the best strategies for them. Furthermore, asthe results of the present study imply, students feel that campus is the place for providinginformation on learning strategies so that everyone could have access to that information.Naturally, lecturers would be the ones to offer that information.Key words: Vocabulary, Learning Strategy,and Motivation.